Effect of dope extrusion rate on morphology and performance of hollow fibers membrane for ultrafiltration - Ismail, A. F.; Mustaffar, M. I.; Illias, R. M.; Abdullah, M. S. (Elsevier, 2006)
The objective of this study is to determine the effects of dope extrusion rate (DER) on polyethersulfone hollow fiber ultrafiltration membrane performance and morphology. The hollow fiber ultrafiltration membranes were produced by using a simple dry/wet spinning process with forced convection in the dry air gap. A newly developed dope solution consists of 20.6 wt.% polyethersulfone (PES), 63.6 wt.% 1- methyl-2-pyrrolidone (NMP), 9.3 wt.% polyethylene glycol (PEG) and a mixture of potassium acetate and water (20/80 wt.%) was used as a bore fluid in this study. This newly developed dope solution was designed to be very close to its cloud point (binodal line) in order to speed up the coagulation process so that the relaxation effect on molecular orientation can be reduced. The dope extrusion rate was varied from 2.0 to 4.0 cm3/min with 0.5 cm3/min increments in order to study the effect of DER on fiber performance and morphology. The experimental results showed that the flux of the hollow fiber ultrafiltration membranes decreases while the separation performance for particular solute increases with an increase in dope extrusion rate. This suggests that the outer skin layer of the membranes becomes apparently thicker and denser with increasing dope extrusion rate. Once the separation performance reaches maximum (critical point), the rejection decreases with increasing dope extrusion rate, observed possibly due to formation of less tighten outer skin structure at high dope extrusion rate. Plane-polarized Fourier transform infrared spectroscopy revealed that membrane spun at dope extrusion rate of 3.5 cm3/min showed largest spectrum difference suggesting that higher molecular orientation is responsible for an enhanced separation performance. This study also indicated that ultrafiltration hollow fiber membrane produced has a high potential to be used for cyclodextrin separation.